Productivity Growth in China's Agriculture During 1985–2010 - Zhou LI; Hai-peng ZHANG (Journal of Integrative Agriculture, 2013)
This paper made an empirical analysis of China's agricultural growth path and influential factors using the province-level panel data of agricultural inputs and outputs during 1985–2010. The findings indicate that the increase in agricultural inputs and TFP contributed 40.6 and 55.2% to the agricultural output growth, respectively; China's agriculture had jumped out of the pattern which output growth was mainly driven by increasing input. Of the total inputs, chemical fertilizer had the most important contribution to the output growth, followed by mechanical inputs. The contribution of land and labor was negative. China's agricultural output growth belonged to the type of induced technology innovation. China's agricultural TFP growth had characteristics of fluctuations over time and unbalanced between regions, but the gap between the eastern, the middle, and the western regions has been narrowed.